2016
DOI: 10.1037/prj0000168
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness sexual stigma: Implications for health and recovery.

Abstract: Objective Among people in psychiatric care worldwide, the majority is sexually active, and sharply elevated rates of HIV infection compared to the general population have been shown. Recovery-oriented treatment does not routinely address sexuality. We examined the relationship between gender, severe mental illness diagnosis, and stigma experiences related to sexuality among people in psychiatric outpatient care. Method 641 sexually active adults attending eight public outpatient psychiatric clinics in Rio de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 26 publications
(56 reference statements)
1
42
0
4
Order By: Relevance
“…() and Wainberg et al . () found a relationship between internalized mental health stigma in this group and their choices in sexual relationships, which leads to increased sexual risk behaviour. A recent meta‐analysis also demonstrated that they have elevated rates of HIV (as well as hepatitis B and C) (Hughes et al .…”
Section: Introductionmentioning
confidence: 94%
“…() and Wainberg et al . () found a relationship between internalized mental health stigma in this group and their choices in sexual relationships, which leads to increased sexual risk behaviour. A recent meta‐analysis also demonstrated that they have elevated rates of HIV (as well as hepatitis B and C) (Hughes et al .…”
Section: Introductionmentioning
confidence: 94%
“…Mental illness stigma scale (MISS-Q) [21]: a 32 item tool that has been developed and validated to measure a person's perceived stigma as a result of their mental health problem and its impact on perceptions of attractiveness and opportunities for intimate relationships. EQ-5D-5L (EuroQol): a standardised instrument for use as a measure of health outcome applicable to a wide range of health conditions and treatments (https://euroqol.org)…”
Section: Secondary Outcome Assessmentmentioning
confidence: 99%
“…Este artigo tem como objetivo discutir o fenômeno do delírio a partir da teoria da subjetividade em uma perspectiva histórico-cultural (González Rey, 2003, 2007, 2016. Para tanto, parte-se, à luz de correntes críticas, de reflexões sobre os desdobramentos problemáticos do conceito de delírio na perspectiva psiquiátrica hegemônica, para a qual se toma como referência a quinta edição do Diagnostic and Statistical Manual of Mental Disorders (DSM5).…”
Section: Résuméunclassified